2014
DOI: 10.1155/2014/841480
|View full text |Cite
|
Sign up to set email alerts
|

Actinomyces graevenitzii Pulmonary Abscess Mimicking Tuberculosis in a Healthy Young Man

Abstract: Pulmonary actinomycosis is a rare disease that is often misdiagnosed as tuberculosis or lung cancer. Actinomyces graevenitzii is a relatively new recognized Actinomyces species isolated from various clinical samples. The authors report a case of pulmonary actinomycosis caused by A graevenitzii. A computed tomography examination revealed an excavated consolidation in the middle right lobe of a previously healthy young man who presented with a long history of moderate cough. Cultures of the bronchoalveolar lavag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 14 publications
3
20
0
Order By: Relevance
“…This may be due to the racial difference in the oral microbiome. Such racial difference has been reported in earlier studies of the vaginal microbiome [54,55].…”
Section: Discussionsupporting
confidence: 76%
“…This may be due to the racial difference in the oral microbiome. Such racial difference has been reported in earlier studies of the vaginal microbiome [54,55].…”
Section: Discussionsupporting
confidence: 76%
“…that have a predilection for causing invasive infections at specific body sites (2). Our study confirmed previous reports of the association of A. graevenitzii with pulmonary infections (33,34) and of A. radingae with SSTA infections of the upper body associated with chest or breast abscesses (35). In our study, we found that A. odontolyticus was the most common and diverse cause of invasive actinomycosis, including intraabdominal abscesses, osteomyelitis, pulmonary infections, and sepsis.…”
Section: Discussionsupporting
confidence: 92%
“…Differentiation between these entities can be challenging. 27 We suggest actinomycosis should be kept in mind. Despite the causative organism does not play any role for initial surgical treatment gathering of samples at that point of time including tissue and liquid samples for diagnostics is crucial for the patient and the continuative therapy.…”
Section: Discussionmentioning
confidence: 93%